TANGGUNG JAWAB DIREKTUR PT PMA YANG TIDAK MENDAPATKAN PENGESAHAN SEBAGAI BADAN HUKUM DAN SUDAH MENJALANKAN USAHANYA BERDASARKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA (STUDI KASUS PT.X DAN PT.Y) - I Gede Putra Wijaya; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2018)
Foreign investors who want to invest in Indonesia must obey the existing rules, namely the Investment Law No. 25 of 2007. The investment law stipulates that if foreign investors want to do business in Indonesia, the foreign investor must establish a company in the form of a legal entity, namely a limited liability company. Requirements for foreign companies can be said as legal entities that must go through the stages of establishing a company until the company ratified by the Ministry of Law and Human Rights. If a foreign company is not a legal entity, the foreign company is not legal and cannot be considered a legal subject in carrying out business activities in Indonesia. Regarding the liability of the foreign company that is to be borne by the private party not by the shareholders because the foreign company is not a legal entity. It is better if foreign investors want to carry out business activities in Indonesia that the business must be in the form of a legal entity in accordance with the investment law’s order to comply with the applicable rules and foreign investors can carry out their business activities properly.